2008
DOI: 10.1021/jm701585h
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationship Study on Anti-HIV 6-Desfluoroquinolones

Abstract: On the basis of our recent findings that 6-aminoquinolones inhibit the HIV Tat-mediated transactivation, we have designed a broad series of derivatives identifying novel potent agents such as the 6-desfluoroquinolones 24 (HM12) and 27 (HM13), which showed pronounced anti-HIV activity in acutely, chronically, and latently HIV-1 infected cell cultures. We demonstrate here that highly potent molecules can be obtained by optimizing the substituent in the various positions of the quinolone nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…The 6-hydrogen derivative maintained low cytotoxicity but exhibited a 6-fold decrease in antiviral activity ( Table 1), indicating that the amino group in the C-6 position is important for preserving potent anti-HCMV activity. This is in agreement with recent reports on other 6-hydrogen-1-methylquinolones, which were found to be inactive against HCMV (39). To explore the importance of the carboxylic substituent at the C-3 position, the anti-HCMV activity of WC5E, the ethyl ester analogue of the lead compound, WC5 (9), was also tested.…”
Section: Resultssupporting
confidence: 88%
“…The 6-hydrogen derivative maintained low cytotoxicity but exhibited a 6-fold decrease in antiviral activity ( Table 1), indicating that the amino group in the C-6 position is important for preserving potent anti-HCMV activity. This is in agreement with recent reports on other 6-hydrogen-1-methylquinolones, which were found to be inactive against HCMV (39). To explore the importance of the carboxylic substituent at the C-3 position, the anti-HCMV activity of WC5E, the ethyl ester analogue of the lead compound, WC5 (9), was also tested.…”
Section: Resultssupporting
confidence: 88%
“…Subsequent structural investigations on a number of analogues of the lead compound WM5 allowed us to obtain insights into their structure-activity relationships (44). We successfully eliminated the amino group from the C-6 position and positioned a suitable 4-arylpiperazine at the C-7 position, resulting in the development of a new series of potent 6-DFQs (45). Indeed, we found that substitution at the N-4 piperazine core of m-trifluoromethylphenyl (HM-12) or benzothiazole (HM-13) resulted in pronounced anti-HIV properties, particularly in M/M cell lineages, with EC 50 values in the ng/ml range.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2,5] Benzothiazolyl derivative 12 showed good anti-HIV activity which, however, was not perfectly reproducible, whereas 13, bearing the pyridinylpiperazine as a C7 substituent, showed moderate activity coupled with low cytotoxicity leading to positive SI values.…”
Section: Biological Activitymentioning
confidence: 99%